Fashionable childhood children in advertising - Vanska, Annamari; Malkki, Eva (London Bloomsbury, 2017)
"Fashionable Childhood is the first book to critically examine representations of children and childhood through fashion media. Focussing on themes such as innocence, sexuality, class, and gender, this book provides a detailed and fascinating overview of the topic over the last 40 years"--Provided by publisher.
1. Historically Constructed Childhood -- 2.Fashionable Childhood -- 3.Innocent Children -- 4.Eroticized Innocence -- 5.Fashion as the Sexualizer of Children? -- 6.Heterosexual Innocence -- 7.Queer Children in Fashion Advertising -- 8.Sexualization is the Name of the Game -- Epilogue: The Right to One's Own Style -- Bibliography -- Index.
This is an english translation of Muodikas lapsuus: Lapset muotikuvissa by the same author, published in 2012.
Includes bibliographic references and index.
Keywords: Children in advertising; Advertising -- Psychological aspects; Advertising -- Children's clothing; Mass media and children